The current state of female leadership in the United Arab Emirates - Kemp, Linzi (2013)
Purpose: To research the state of affairs in the United Arab Emirates (UAE) for the presence (or absence) of women in senior business leadership positions, and to investigate where they are located within organizations (e.g., board members, chief officers, vice presidents, top management, division or unit heads). Design/methodology/approach: This is a quantitative gender analysis of 954 organizations, based on data available from the Zawya database that tracks information about public and private companies in the Middle East and North Africa (MENA) region. Findings: Women are still underrepresented in senior company and top department leadership positions; however, they are found slightly (but not significantly) more in departmental leadership, pseudo services and hospitality industries, and in smaller and public companies. Research limitations: The database utilized did not contain completed company data; specifically, any response variable; hence, the study was descriptive in nature and lacked advanced statistical techniques for comparison and relationship analysis. Practical implications: This study provides helpful insights for government leaders, educators, and scholars who work to help prepare women for leadership in this region. For business practitioners, the presence and development of female business leaders extends choice and increases value in the human resource pool. Social implications: The authors believe that it is important that UAE females take up roles in both the public and private sector so they can become more effective role models to a rising generation of female workers. Originality/value: This is one of the first scholarly studies conducted on the presence of women leaders in various sectors within the UAE.